Researches regarding the confirmation of sunflower hibrises by influence of technological verifications in the south water area of Romania - Florentina Eremia (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 8th Edition of the International Symposium, November 2017, Bucharest, 2017)
The main purpose of this paper is to determine the best sunflower hybrids (Helianthus annuus) suitable for the southern part of Romania, which under different conditions of fertilization and technology will lead to the achievement of large and stable productions. The experience was located at INCDA Fundulea, on a uniform chernozem soil in terms of fertility and microrelief. The experimental module was of the trifactor type and was arranged according to the subdivision parcel method in three rehearsals. The cultivation of the plants was carried out under optimum conditions, specific to the culture area, in the non-irrigated version, the genotypes taken into study consisting of three hybrids: Performer, Barolo RO and PR64A89. The conclusions are to determine the associated influence of three crop factors, namely plant density, fertilization and hybrid influence on sunflower production under the climatic year 2013.
Keywords: 330; sunflower; technological links; production; quality